Effectiveness of a web‐based treatment decision aid for men with lower urinary tract symptoms due to benign prostatic hyperplasia. (4th March 2019) - van der Wijden, Fieke C.; de Angst, Isabel B.; Lamers, Romy E.D.; Cuypers, Maarten; de Vries, Marieke; van Melick, Harm H.E.; de Beij, Jeltje S.; Oerlemans, Dennis J.A.J.; van de Beek, Kees; Kil, Paul J.M.
Abstract : Objectives: To evaluate the effectiveness of a web‐based decision aid (DA), with values clarification exercises compared with usual care, for men with lower urinary tract symptoms due to benign prostatic hyperplasia (LUTS/BPH). Patients and Methods: Between July 2016 and January 2017, all new patients with LUTS/BPH who consulted the urologist were invited to use the DA and participate in this prospective questionnaire study. Patients who consulted the urologist between December 2015 and February 2016 served as controls. The DA was designed to support patients in making a well‐informed treatment decision, corresponding with their personal preferences and values. Well‐informed decision was measured by using a knowledge questionnaire. Value congruent decision was measured by the correspondence between responses on nine value statements and chosen treatment. The primary outcome, decision quality, was defined as the combination of well‐informed decision and value congruent decision. Secondary outcomes were decisional conflict, involvement and received role in shared decision‐making, decisional regret, and treatment choice. Results: A total of 109 DA‐users and 108 controls were included. DA‐users were younger (68.4 vs 71.5 years; P = 0.003) and their education level was higher ( P = 0.047) compared with the controls. Patients who used the DA made a well‐informed and value congruent decision more often than the control group (43% vs 21%; P = 0.028). DA‐users had less decisional conflict (score 33.2 vs 46.6; P = 0.003), experienced a less passive role in decision‐making (22% vs 41%; P = 0.038), and reported less process regret (score 2.4 vs 2.8; P = 0.034). Furthermore, DA‐users who had not used prior medication chose lifestyle advices more often than the control group (43% vs 11%; P = 0.002). Outcomes were adjusted for significantly different baseline characteristics. Conclusion: The LUTS/BPH DA seems to improve the decision quality by supporting patients in making more well‐informed and value congruent treatment decisions. Therefore, further implementation of this DA into routine care is suggested.